Effectiveness of Yoga to Improve Psychological Health in Geriatry: A Systematic Review - Hadiyati, Fathmi; Nurjanah, Suci; Iswari, Putu Wika Pramesti; Syifa, R.R. Ditya Mutiara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The elderly population brings about the appearance of multi disorder, physical or psychological health. These disorders may tried to be prevented before symptoms and improve the quality of life. This study aims to estimate the effectiveness of Yoga on the psychological health in geriatrics. The research design was systematic review, four electronics databases were searched up to January 2023. The review included Randomized controlled trials (RCTs). The main outcome was psychological health. The risk of bias was evaluated with the Cochrane Risk of Bias tool. Data from the primary studies were combined using a random-effects model, and subgroup analysis was performed based on the type of exercise conducted. A total of 898 studies examined, there were five studies aged at least 60 years were included. The interventions had an average duration ranging from 6 to 12 weeks. The results indicated that significant differences were found in the effectiveness of yoga on psychological health in the elderly. Although there are various types of yoga that are given, the effect of yoga on psychological health in the elderly has a significant effect. It is necessary to adjust the type of yoga with the elderly population with various characteristics.